Gambaran Persepsi Pejabat Gereja Bethel Injil Sepenuh (GBIS) Majelis Daerah Jawa Tengah tentang Pandemi Covid-19 dan Implikasinya bagi Pelayanan Gerejawi - Setiawan, David; Purwoto, Purwoto; Stevanus, Kalis (Kharisma: Jurnal Ilmiah Teologi, 2020)
This research was motivated by the difference in perceptions among GBIS officials of the Central Java Regional Council about the Covid-19 pandemic. This difference has implications for ecclesiastical service. The research problem in this research is what is the perception of the Central Java Regional Council GBIS officials about the Covid-19 pandemic and its implications for ecclesiastical services? Meanwhile, the purpose of this study is to explain the perceptions of the Central Java Regional Council GBIS officials about the Covid-19 pandemic and its implications for ecclesiastical services. From the research, it was concluded that the perceptions of the Central Java Regional Council GBIS officials regarding the Covid-19 pandemic were good and adequate. The implication is in ecclesiastical services, GBIS officials in the midst of this pandemic, continue to emphasize that hospitality as a pastor must be carried out wisely and correctly so as not to exacerbate Covid-19 transmission without having to lose the human side which of course still requires love and hospitality.Penelitian ini dilatarbelakangi oleh adanya perbedaan persepsi di kalangan para pejabat GBIS Majelis Daerah Jawa Tengah tentang pandemi Covid-19. Perbedaan tersebut berimplikasi bagi pelayanan gerejawi. Problem research dalam penelitian ini adalah bagaimanakah persepsi para pejabat GBIS Majelis Daerah Jawa Tengah tentang pandemi Covid-19 dan implikasinya bagi pelayanan gerejawi? Sedangkan tujuan penelitian ini adalah menjelaskan persepsi para pejabat GBIS Majelis Daerah Jawa Tengah tentang pandemik Covid-19 dan implikasinya bagi pelayanan gerejawi. Dari penelitian tesrebut ditarik kesimpulan bahwa persepsi para pejabat GBIS Majelis Daerah Jawa Tengah berkenaan dengan pandemi covid-19 caik dan memadai. Implikasinya dalam pelayanan gerejawi, para pejabat GBIS di tengah masa pandemi ini, tetap mengetrapkan hospitalitas sebagai gembala sidang harus dilakukan dengan bijak dan benar agar tidak memerparah penularan Covid-19 tanpa harus menghilangkan sisi kemanusiaan yang tentunya tetap membutuhkan kasih dan keramahtamahan.